Prevalence and factors associated with incontinence-associated dermatitis in Pediatric Units (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To estimate the prevalence of and factors associated with the occurrence of incontinence-associated dermatitis (IAD) in children. Method: This observational, cross-sectional study used a quantitative approach and electronic medical record data. It included data from patients aged 0 to 14 years who had been hospitalized for at least 24 hours in pediatric units of a tertiary hospital in the state of São Paulo, Brazil, between January 2021 and December 2022. Descriptive analysis and Poisson regression models were used. Results: The sample consisted of 297 patients with some type of skin lesion, of whom 31.9% (n=95) had IAD. Significant associations were identified between IAD and age, type of hospitalization, comorbidities, medications acting on the cardiovascular system, systemic anti-infective agents, vitamins, and diaper use. The likelihood of developing IAD was 1.87 times higher among patients with preexisting comorbidities, 3.98 times higher among those receiving anti-infective agents, and 2.79 times higher among those using diapers. Conclusion: The prevalence of IAD was 31.9%. Therefore, identifying associated factors is essential for planning preventive strategies aimed at reducing the risk and occurrence of IAD.